Linguistics constructions of the poetry of 1919 revolution - Ali, Emad Abdul Baqi (Arab Journal for Sciences and Research Publishing, 2016)
The purpose of the study is to know the lexicon of the poetry of the 1919 revolution and the relationship between these structures and the culture of the author himself; to find out the contribution of linguistic construction to poetry in the emergence of a new set of conventional structures. The methodology of research requires the adoption of descriptive analysis method of linguistic structures in the poetic sentence through the structural description of each structure to know its linguistic significance. The research consists of an introduction and two axes; it revolves around the linguistic structure of poetry, its relation to the linguistic vocabulary of the revolution, and the influence and being influenced existing between the linguistic significance of poetry and the emerging structures that emerged in society. The conclusion is that it draws a link between the linguistic structure of the language of poetry and the new structures that appeared in the lexicon of the 1919 revolution; to consider the poetic syntax and to identify the linguistic features and new features that emerged in the poetry of the revolution.
Keywords: linguistic structure; semantic structure; lexical significance; language of poetry and revolution